Macro/micro-pore structure characteristics and the chloride penetration of self-compacting concrete incorporating different types of filler and mineral admixture - Mohammed, Mahmoud khashaa; Dawson, Andrew; Thom, Nicholas (Elsevier, 2014)
The relationship between the internal pore structure features at different scales and the local micro-characteristics of the interfacial transition zone (ITZ) to the non-steady state chloride migration coefficient (Dnssm) is investigated for one normal and three types of sustainable high performance self-compacting concrete mixes. The pore structure classification at different scales and the percolation degrees of the ITZ’s pores were determined using both vacuum-saturated and Mercury Intrusion Porosimetry (MIP) techniques. Further, the local micro-permeation features of the ITZ, such as thickness, porosity and the chemistry of its hydration products is examined using the SEM coupled with the EDX analysis on polished, carbon-coated, flat specimens. Chloride movement was achieved using a modified rapid migration test.